Numerical analysis of gasification characteristics in combined coal gasification and flash ironmaking process. (5th May 2020) - Yang, Yiru; Guo, Lei; Li, Dongyue; Guo, Zhancheng
Abstract: The combined coal gasification and flash ironmaking process has been stated as a type of multi-generation system, which can be employed to obtain metallic iron and qualified synthesis gas simultaneously. In this study, a separate coal gasification process under the unique conditions of the multi-generation system was investigated using a numerical method. Turbulent flow, heat transfer, and chemical reactions were included in the computational fluid dynamics (CFD) model to predict the internal velocity field, temperature distribution, component distribution, and carbon conversion rate. The simulation results revealed the gasification characteristics in the multi-generation system; these were compared with the results obtained for the traditional gasification process. The sudden expansion structure divided the velocity field into three regions: jet zone, recirculation zone, and plug flow region, in which the stable turbulent structure was formed. The unheated oxidant and inert carrier gas N2 were injected directly to suppress the extremely high temperatures during the pure oxygen-entrained gasification process without a traditional coolant, such as H2 O or CO2 . A high-quality syngas was obtained with a lower consumption of pure oxygen, and the effective-gas ratio reached 91.73% when the optimum oxygen/coal rate was 0.7. The slender shaft was proven effective for the gasification process to match the subsequent reduction process.